Ultrasound-Assisted Extraction of Antioxidant Compounds from “Cẩm” Purple Rice Bran for Modulation of Starch Digestion - Le Thi Kim Loan; Nguyễn Minh Thủy; Ngô Văn Tài (International Journal of Food Science, 2023)
mol Fe (II)/g. The established models were validated and exhibited a strong alignment between predicted and actual values, with disparities of less than 3% under optimal conditions. Furthermore, the extract was codigested with cooked corn starch, revealing a dose-dependent effect on starch digestibility. The sluggishness of digestion rate was observed when 20 mg of the extract was supplemented to 200 mg of cooked corn starch. This suggests that rice bran extract holds promise as an effective ingredient for mitigating starch digestion, particularly beneficial for individuals dealing with diabetes.
Keywords: Phytochemicals and Antioxidant Activities; Microbial Metabolism and Applications; Food composition and properties